FACTORS AFFECTING THE EXPENDITURE OF FOREIGN TOURISTS THE EVIDENCE FROM INDONESIA - Filda Rahmiati; Rika Misnawati (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTTourist expenditure could determine the probability obtained by the country, which willaffect economic activities. This study examines the Length of stay, Accommodation, Travel Purpose,and Occupation that affect foreign tourist expenditure in Indonesia. The study uses secondary datafrom the Indonesia Ministry of Tourism from the year 2013 – 2016 of 34 countries with 136 totalsamplings. This study using quantitative research. Analysis of the data collected using multipleregression. The hypothesis testing analysis method uses the T-test, F-test, and coefficient ofdetermination (R2). This study says that all variables (Length of stay, accommodation, travelpurpose, and occupation) have a significant effect on daily tourist expenditure partially andsimultaneously; hence, Length of stay has a negative effect. The simultaneous effect was 58%,and 42% are affected by other variables.Keywords: Foreign Tourist Expenditure, Length of stay, accommodation, travel purpose,occupation